Methanolic Extract of Aerva javanica Leaves Prevents LPS-Induced Depressive Like Behavior in Experimental Mice - Arshad HM; Ahmad FUD; Lodhi AH (Dove Medical Press, 2022)
Hafiza Maida Arshad, Fiaz-ud-Din Ahmad, Arslan Hussain Lodhi Department of Pharmacology, Faculty of Pharmacy, the Islamia University of Bahawalpur, Bahawalpur, PakistanCorrespondence: Fiaz-ud-Din Ahmad, Department of Pharmacology, the Islamia University of Bahawalpur, Pakistan Khawaja Fareed Campus, Railway Road, Bahawalpur, 63100, Pakistan, Tel +92-320-8402376, Email fiaz.ahmad@iub.edu.pkAim: Depression is a chronic recurrent neuropsychiatric disorder associated with inflammation. This study explored the pharmacological activities of Aerva javanica leaves crude extract (Aj.Cr) on lipopolysaccharide (LPS)-induced depressive-like behavior in experimental mice.Methods: Aj.Cr was evaluated for its phenolic and flavonoid contents, bioactive potential, amino acid profiling and enzyme inhibition assays using different analytical techniques followed by in-silico molecular docking was performed. In addition, three ligands identified in HPLC analysis and standard galantamine were docked to acetyl cholinesterase (AchE) enzyme to assess the ligand interaction along with their binding affinities. In in-vivo analysis, mice were given normal saline (10 mL/kg), imipramine (10 mg/kg) and Aj.Cr (100, 300, and 500 mg/kg) orally for 14-consecutive days. On the 14th day, respective treatment was given 30-minutes before intra-peritoneal administration of (0.83 mg/kg) LPS. Open field, forced swim and tail suspension tests were performed 24-hours after LPS injection, followed by a sucrose preference test 48-hours later. Serum corticosterone levels, as well as levels of nitric oxide (NO), malondialdehyde (MDA), glutathione (GSH), superoxide dismutase (SOD), catalase (CAT), tumor necrosis factor-alpha (TNF-), interleukin-1β (IL-1β), interleukin-6 (IL-6), brain-derived neurotrophic factor (BDNF) and catecholamines were determined in brain tissues.Results: In-vitro results revealed that crude extract of Aj.Cr possesses anti-depressant agents with solid antioxidant potential. In-vivo analysis showed that LPS significantly increased depressive-like behavior followed by alteration in serum and tissue biomarkers as compared to normal control (p < 0.001). While imipramine and Aj.Cr (100, 300, and 500 mg/kg) treated groups significantly (p< 0.05) improved the depressive-like behavior and biomarkers when compared to the LPS group.Conclusion: The mitigation of LPS-induced depressive-like behavior by Aj.Cr may be linked to the modulation of oxidative stress, neuro-inflammation and catecholamines due to the presence of potent bioactive compounds exerting anti-depressant effects.Keywords: Aerva javanica, depression, lipopolysaccharide, oxidative stress